The Dyadic Effects of Relationship Uncertainty on Negative Relational Maintenance. (2nd September 2017) - Dainton, Marianne; Goodboy, Alan K.; Borzea, Dana; Goldman, Zachary W.
Abstract : This study examined the dyadic effects of relationship uncertainty and the use of negative relational maintenance behaviors. Romantic couples ( N  = 227 dyads) completed a survey assessing their current relationship uncertainty (i.e., definition, mutuality, behavioral, future) and their use of negative behaviors to maintain their relationship (i.e., jealousy induction, avoidance, spying, infidelity, destructive conflict, allowing control). Multilevel modeling was used to calculate actor-partner interdependence models. Actor effects were revealed between relationship uncertainty and negative relational maintenance. Results also revealed some partner effects. However, nine of these effects were moderated with significant actor-by-partner interactions, indicating that actors and partners with low relationship uncertainty use less negative maintenance in their relationships.